Peranan Self Efficacy dan Konsep Diri terhadap Perilaku Menyontek pada Mahasiswa Universitas Muhammadiyah Sidoarjo - Pratiwi, Nuryl Dwi; Affandi, Ghozali Rusyid (Universitas Muhammadiyah Metro, 2023)
Cheating behavior is a dishonest act deliberately carried out by someone to gain approval from others for their learning achievements, even if it is done incorrectly. This research aims to review the role of self-efficacy and self-concept on students' cheating behavior at Muhammadiyah University of Sidoarjo. Using a simple random sampling technique, the research design used a quantitative approach with a sample of 370 students at Muhammadiyah University of Sidoarjo. This research instrument uses an adoption and adaptation scale with a Likert scale model on cheating behavior, self-efficacy, and self-concept. The cheating behavior scale was adopted from Muni Pratiwi (2015) based on behavioral aspects according to Fishbein and Ajzen (1975) with a Cronbach's Alpha reliability of 0.888. The self-efficacy scale is measured using the General Self-Efficacy Scale developed by Born, Schwarzer & Jerusalem (1999), which has been adapted into Indonesian by Riangga Novrianto (2019) with a Cronbach's Alpha of 0.901. Self-concept was measured using the adoption of the Tennessee Self-Concept Scale (TSCS) created by Fitts (1971) and developed in Indonesian by Shovia Lintina (2015). The data analysis technique uses multiple linear regression. The research results state that self-efficacy and self-concept play a role in cheating behavior. When students feel confident in achieving achievements and can complete academic activities well, it will enable students to engage in less cheating behavior. The contribution made jointly was 40.9%. Self-efficacy contributed 32%, while self-concept contributed 8.7%, which means self-efficacy contributed more to cheating behavior.